MENUMBUHKAN JIWA KEWIRAUSAHAAN MANDIRI DAN BERFIKIR INOVATIF MELALUI PEMBERIAN PENGALAMAN NYATA PADA SISWA SMA N 1 GUNUNG TALANG KABUPATEN SOLOK - Dwi Putri, Tyara; Azliyanti, Elfitra; Utami, Wiry; Putri, Refallis Alya; Nikmah, Irma Muhimmatun; Julia, Julia (Komunitas Manajemen Kompetitif, 2024)
The purpose of this activity is to develop entrepreneurial skills. With independent entrepreneurship, it is envisaged that recent high school graduates will have more chances to hone their entrepreneurial abilities in marketing, finance, planning, and invention, among other areas. Through entrepreneurial experience, high school graduates can develop a tough spirit and resilience that is useful not only in a business context but also in everyday life. The method used by the PKM Team is face to face. Activity provided participants with the time and opportunity to directly practice making crafts from feather wire. We hope that this training will boost students' confidence in generating innovative ideas for potential business ventures, ultimately fostering an independent entrepreneurial spirit among students at SMA Negeri 1 Gunung Talang, Solok Regency.